Analysis of Transformer Dielectric Quality at the Kisaran Main Substation of PT. PLN (Persero) ULTG Kisaran - Rizinski Khaliksi; Parlin Siagian; Zuraidah Tharo (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study presents a comprehensive analysis of the dielectric quality of a 60 MVA power transformer at the Kisaran 150kV Substation, North Sumatra, Indonesia. The transformer, manufactured by PAUWELS TRAFO and operated since 2011, operates at an average load of 33% with an ONAN/ONAF cooling system. Dielectric testing yielded a breakdown voltage of 80.2 kV, a moisture content of 17.62 mg/kg, an acid number of 0.108 mgKOH/g, and dissipation factors of 0.173% (primary), 0.190% (secondary), and 0.243% (tertiary). The bushing dissipation factor ranged from 0.247% to 0.271%. The interfacial tension measured 26.8 mN/m with a flash point at 148°C. Insulation resistance testing showed values of 4.9 GΩ (primary), 3.41 GΩ (secondary), and 3.40 GΩ (tertiary) with polarization indices of 3.06, 1.48, and 1.47, respectively. Operating temperatures remained within acceptable limits at 63°C (peak oil) and 62°C (winding). Analysis based on IEC 60422:2013 and PLN standards indicated that the transformer was in good operational condition with all parameters within acceptable ranges, although the interface voltage was close to the warning threshold. This study provides valuable baseline data for predictive maintenance strategies and demonstrates the importance of integrated dielectric testing for transformer health assessment.